A search for origins : science, history and South Africa's Cradle of Humankind - Bonner, P. L.; Esterhuysen, Amanda; Jenkins, Trefor (Geneticist) (Wits University Press, 2007)
The 'Cradle of Humankind' (COH), bordering Gauteng and the NorthWest Province, was declared a World Heritage Site for the wealth of the human and animal fossils found there. Research based on fossils found in the area as well as signs of early human habitation have shed new light on the evolution of humankind and on the significant role that southern Africa played in the development of modern humans. A Search for Origins aims to provide an overview of the history of the COH, and of the important discoveries that have been made there, for a nonspecialist audience. A number of general accounts have been written which have concentrated on the palaeontological discoveries made there. No systematic account written by specialists in their disciplines has, however, been published about the wider history of the COH and surrounding areas. In particular, no overview spanning the evolution of early plant and animal life, human development and recent and colonial history as reflected in discoveries linked to the COH, has been attempted. This edited volume frames the scientific advances that have been made in the COH against the intellectual and political background out of which they emerged. The multidisciplinary approach - from a wide range of specialists - is innovative and groundbreaking.--